Big data in computational social science and humanities: edited by Chen, S., Cham, Springer, 2018, 388 pp., €117.69 (ebook), ISBN 978-3-319-95465-3. - Zhao, Zhenhua; Feng, Guohua (Innovation: The European Journal of Social Sciences, 2025)
The article discusses the edited volume "Big Data in Computational Social Science and Humanities," which explores the impact of big data on various disciplines within social sciences and humanities. It highlights the challenges researchers face in utilizing data analytics techniques and emphasizes the book's role in bridging gaps between these fields. The volume is structured into two parts, featuring nineteen scholarly works that cover applications of big data in areas such as economics, psychology, and literature, while also addressing methodological innovations and practical applications. Overall, the book serves as a valuable resource for a diverse audience, including social scientists, humanists, and students, aiming to enhance their understanding and use of big data in research.